2015
DOI: 10.1091/mbc.e15-04-0203
|View full text |Cite
|
Sign up to set email alerts
|

TβRIII independently binds type I and type II TGF-β receptors to inhibit TGF-β signaling

Abstract: Study of the TβRIII interaction with the signaling TGF-β receptors shows that TβRIII homo-oligomerization is indirect, depending largely on interactions with GIPC scaffolds. TβRI and II bind independently to TβRIII, competing with TβRI-TβRII complex formation and inhibiting Smad2/3 signaling by a mechanism independent of TβRIII ectodomain shedding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 56 publications
6
38
0
Order By: Relevance
“…18). These data suggest that the oncogenic effect of TGFBR3 overexpression in MECA is mediated by mechanisms independent of TGF-ß signaling, which is in line with previous findings in breast cancer (43).…”
Section: Detection Of a Novel Recurrent Tgfbr3-plag1 Fusionsupporting
confidence: 92%
See 1 more Smart Citation
“…18). These data suggest that the oncogenic effect of TGFBR3 overexpression in MECA is mediated by mechanisms independent of TGF-ß signaling, which is in line with previous findings in breast cancer (43).…”
Section: Detection Of a Novel Recurrent Tgfbr3-plag1 Fusionsupporting
confidence: 92%
“…TGFBR3 can act as a tumor suppressor which acts negatively on TGF-ß signaling by binding to TGFBR1 and TGFBR2 separately, thereby inhibiting the TGFBR1/2 complex formation (43). On the other hand, overexpression of TGFBR3 has oncogenic potential in breast and colorectal cancer (44,45).…”
Section: Detection Of a Novel Recurrent Tgfbr3-plag1 Fusionmentioning
confidence: 99%
“…Nevertheless, the mechanism by which the high level of TGF-β1 exerts tumorpromoting effects remains unclear. A recent study found that TβRIII inhibited TGF-β-mediated signaling through the independent binding to TβRI and TβRII and competition with TβRI/TβRII complex formation (15). We found decreased expression of TβRIII concomitant with the elevated level of TGF-β1, as well as the role of TGF-β1 in promoting metastasis in the HCC cell lines.…”
Section: Discussionsupporting
confidence: 52%
“…Overexpression of TβRIII was found to restore TGF-β1 sensitivity in CAL-27 human oral squamous cells (14). In MDA-MB-231 human breast cancer cells, TβRIII expression inhibited Smad2/3 signaling dependent on the TβRIII cytoplasmic domain, and the independent binding of TβI/TβRII to TβRIII competed with TβI/TβRII signaling complex formation, thus inhibiting TGF-β-mediated Smad signaling (15). Importantly, the alteration of TβRIII expression level and the mediating roles have been observed in the progression of several types of cancers including breast, prostate, lung and ovarian cancer (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 94%
“…Betaglycan has been shown to promote both Smad and non-Smad signaling (You et al 2007). However, betaglycan binds TbRI and TbRII independently, and overexpression of betaglycan in MDA-MB-231 cells was found to inhibit TGF-b-induced Smad2 and Smad3 phosphorylation (Tazat et al 2015). Betaglycan is basolaterally located in polarized breast epithelial cells, and loss of the basolateral localization promotes EMT (Meyer et al 2014).…”
Section: Betaglycan/tbriiimentioning
confidence: 99%